GAYA KEPEMIMPINAN TRANSFORMASIONAL, KEADILAN ORGANISASI, DAN REAKSI KARYAWAN TERHADAP KINERJA KARYAWAN - Glenda Avilla (Jurnal Manajemen dan Pemasaran Jasa, 2017)
The background of this study is to analyze the effect of transformational leadership and organizational justice on employee performance through employee reaction. The purpose of this study is to examine the influence of transformational leadership and organizational justice to employee performance through employee reaction in Trisakti Dental Hospital. The design of this research is hypothesis testing using primary data obtained by distributing 200 questionnaires to employees of Trisakti Dental Hospital. The analytical method used is Structure Equation Model (SEM). The result of this research concludes that there is no significant and negative relation between transformational leadership and employee reaction. There is a significant and positive relation between organizational justice and employee reactions. There is a significant and positive relation between employee reactions and employee performance.